(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
Allometric scaling of metabolic rate with body mass is a fundamental feature in insect physiology, yet the scaling relationship often varies across developmental stages due to differences in energy requirements, tissue composition, and metabolic regulation. This study examined the metabolic–mass scaling patterns in the non-diapausing larvae and diapausing pupae of Cirina forda, a widely distributed edible insect of significant ecological and economic importance. Metabolic rate was indirectly determined by measuring oxygen consumption (VO₂) through respirometry and carbon dioxide evolution (VCO₂) via titrimetric analysis. The relationship between body mass and metabolic rate was evaluated using Least Squares Regression (LSR) of log-transformed data (Log₁₀VO₂ vs. Log₁₀Mass). Analysis of Variance (ANOVA), t-tests, and coefficients of determination (R²) were employed to assess the goodness of fit, compare regression slopes, and evaluate the explanatory power of each regression model. All regression models yielded statistically significant results, indicating strong mass-dependent metabolic patterns across developmental stages. However, the slopes (scaling exponents) of regression lines for larval instars were not significantly different from one another, suggesting consistent metabolic scaling during larval development. In contrast, the slopes of regression lines for pupae aged 90–120 days were significantly different from earlier pupal stages, showing a marked decline in metabolic activity. Moreover, a significant difference was observed between larval and pupal regression slopes (t₄₂ = 4.32; P < 0.05), confirming distinct allometric relationships between the two life stages. The negative slopes observed in late pupae indicate a reduction in metabolic intensity with increasing mass, likely reflecting metabolic suppression during diapause. These findings highlight that the allometric scaling of C. forda is strongly stage-dependent, shaped by developmental physiology and adaptive energy conservation mechanisms. Understanding these patterns contributes to broader insights into insect bioenergetics and developmental ecology.